Plant Metabolic Gene Clusters: Evolution, Organization, and Their Applications in Synthetic Biology - Bharadwaj, Revuru; Kumar, Sarma R.; Sharma, Ashutosh; Sathishkumar, Ramalingam (Frontiers in Plant Science, 2021)
Plants are a remarkable source of high-value specialized metabolites having significant physiological and ecological functions. Genes responsible for synthesizing specialized metabolites are often clustered together for coordinated expression which is commonly observed in bacteria and filamentous fungi. Similar to prokaryotic gene clustering, plants do have gene clusters encoding enzymes involved in biosynthesis of specialized metabolites. More than 20 gene clusters involved in the biosynthesis of diverse metabolites have been identified across plant kingdom. Recent studies demonstrate that gene clusters are evolved through gene duplications and neofunctionalization of primary metabolic pathway genes. Often these clusters are stringently regulated at the nucleosome level. Prevalence of gene clusters related to specialized metabolites offers an attractive possibility of an untapped source of highly useful biomolecules. Accordingly, identification and functional characterization of novel biosynthetic pathways in plants need to be worked out. In this review, we summarize insights on the evolution of gene clusters and discuss the organization and importance of specific gene clusters in the biosynthesis of specialized metabolites. Regulatory mechanisms which operate in some of the important gene clusters have also been briefly described. Finally, we highlight the importance of gene clusters to develop future metabolic engineering or synthetic biology strategies for heterologous production of novel metabolites.